Minnesplatsen som process och performance: Det urbana konstverket - Neuhauser, Charlott (Peripeti, 2012)
In the article, I discuss a visit to the memorial Denkmal für die ermordeten Juden Europas in Berlin using Nicolas Whybrow’s description of his visit to the memorial, and his idea of the performative urban work in the book Art and the City (2010). I also use theatre scholar Willmar Sauter’s term ”playing culture”. My experience of the work and the reading of Whybrow’s text are intertwined in a process which is activating. I suggest that the experience of the memorial is play-like rather than performative.